Understanding Host-Pathogen Interactions in Acute Chorioamnionitis Through the Use of Animal Models - Brosius Lutz, Amanda; Al-Nasiry, Salwan; Kramer, Boris W.; Mueller, Martin (Frontiers in Cellular and Infection Microbiology, 2021)
Inflammation of the chorion and/or amnion during pregnancy is called chorioamnionitis. Acute chorioamnionitis is implicated in approximately 40% of preterm births and has wide-ranging implications for the mother, fetus, and newborn. Large disease burden and lack of therapeutic approaches drive the discovery programs to define and test targets to tackle chorioamnionitis. Central to the advancement of these studies is the use of animal models. These models are necessary to deepen our understanding of basic mechanisms of host-pathogen interactions central to chorioamnionitis disease pathogenesis. Models of chorioamnionitis have been developed in numerous species, including mice, rabbits, sheep, and non-human primates. The various models present an array of strategies for initiating an inflammatory response and unique opportunities for studying its downstream consequences for mother, fetus, or newborn. In this review, we present a discussion of the key features of human chorioamnionitis followed by evaluation of currently available animal models in light of these features and consideration of how these models can be best applied to tackle outstanding questions in the field.